Tribocatalytic behaviour of a TiO2 atmospheric plasma spray (APS) coating in the presence of the friction modifier MoDTC: a parametric study. Issue 27 (20th April 2018) - Deshpande, P.; Minfray, C.; Dassenoy, F.; Le Mogne, T.; Jose, D.; Cobian, M.; Thiebaut, B.
Abstract : Tribocatalytic behaviour of TiO2 APS coatings in presence of MoDTC additive under boundary lubrication conditions – decomposition mechanism Abstract : Recent engine design and emission trends have led to the commercial use of Atmospheric Plasma Spray (APS) coatings for cylinder liner applications like the TiO2 APS coating. It was shown in our previous work that this type of coating showed better friction results compared to steel lubricated with MoDTC. To further investigate this feature, a parametric study was carried out involving the effect of MoDTC concentration, test temperature, Hertzian contact pressure and the change of counterpart materials from steel balls to ceramic balls (Al2 O3 and ZrO2 ). Ball-on-flat tribotests were carried out on a reciprocating (ball-on-flat) tribometer lubricated with base oil containing MoDTC. Results show that for all the test conditions used including the concentration of MoDTC, test temperature and the contact pressure, lower friction and wear is observed for the TiO2 APS coating compared to reference steel. To explain the low friction behavior, tribofilm compositions were investigated and it was observed that MoS2 is always formed in the case of TiO2 APS with no oxysulphide species. For the reference steel, MoO x S y species are mainly detected in the tribofilms. XPS analyses performed on TiO2 APS flats when the counterpart material was changed from steel balls to ceramic balls suggested the formation of MoS2 (Mo in +iv oxidation state) and Mo–C (Mo in +iv or +ii oxidation state) species with a negligible amount of MoO3 (Mo in +vi oxidation state). It was also shown that a significant amount of molybdenum atoms inside the tribofilm, originating from MoDTC (Mo in +v oxidation state) were reduced in the tribological contact. A mechanism for the decomposition of MoDTC on the basis of tribocatalytic behaviour hypothesized in our previous work was proposed and discussed.